Takeover waves and its driving factors : evidence from Singapore. - Chan, Yoke Teng. (2010)
In this paper, the neoclassical and behavioral theories – two theories widely hypothesized to drive takeover waves in the United States – are studied under the Singapore context. We first document the existence of clustering of takeovers at the industry level during the 2000 to 2008 period. The rate of takeover activities for each industry in each year is positively related to the degree of misvaluation of the industry, consistent with the behavioral theory. The behavioral theory suggests that takeovers are a form of arbitrage, whereby firms with temporarily overvalued stocks acquire undervalued firms with their inflated stocks. The shareholders of the targets are motivated to accept the bids of their acquirers because they have shorter holding periods than their acquirers. The neoclassical theory, which hypothesizes that takeover waves in a particular industry are linked to the various economic, technological, or regulatory shocks that occurred in the industry, has little explanatory power for takeover waves in our study.